2018
DOI: 10.1530/rep-17-0647
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring uterine contractility in mice using a transcervical intrauterine pressure catheter

Abstract: In mouse models used to study parturition or pre-clinical therapeutic testing, measurement of uterine contractions is limited to either isometric tension or operative intrauterine pressure (IUP). The goal of this study was to: (1) develop a method for transcervical insertion of a pressure catheter to measure intrauterine contractile pressure during mouse pregnancy, (2) determine whether this method can be utilized numerous times in a single mouse pregnancy without affecting the timing of delivery or fetal outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Disturbance of intrauterine contractions at the preimplantation stage causes the aberrant distribution of implanted embryos (Chen et al, 2011). At the end of embryogenesis, uterine muscle contractions deliver embryos, which is also known as labor (Rada et al, 2015;Robuck et al, 2018). Inappropriate uterine muscle contractions cause preterm or delayed labor (Pierce et al, 2008(Pierce et al, , 2010Bond et al, 2000;Padol et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Disturbance of intrauterine contractions at the preimplantation stage causes the aberrant distribution of implanted embryos (Chen et al, 2011). At the end of embryogenesis, uterine muscle contractions deliver embryos, which is also known as labor (Rada et al, 2015;Robuck et al, 2018). Inappropriate uterine muscle contractions cause preterm or delayed labor (Pierce et al, 2008(Pierce et al, , 2010Bond et al, 2000;Padol et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have shown that physical confinement mimicking the uterine environment is crucial to elongation into an egg-cylinder shape (Hiramatsu et al, 2013). Although uterine smooth muscle exerts intrauterine pressures, otherwise known as labor, at delivery in the late stage of a mouse pregnancy (Pierce et al, 2010;Grotegut et al, 2016;Rada et al, 2015;Robuck et al, 2018), its effects during early implantation stages remain unexplored. To address how much mechanical stress is exerted on embryos in utero, we directly measured intrauterine pressures at peri-implantation stages by inserting a microtransducer-mounted catheter into intrauterine space through one side of exposed uterine horn (Figure 5D).…”
Section: Smooth Muscle Contractions Exert High and Periodic Intrauterine Pressures On Embryosmentioning
confidence: 99%
See 3 more Smart Citations